Morphology and Structure of Nb Thin Films Grown by Pulsed Laser Deposition at Different Substrate Temperatures. Issue 11 (November 2016) - Gontad, F.; Lorusso, A.; Manousaki, A.; Klini, A.; Perrone, A.
Abstract : This paper reports the fabrication of Nb thin films through pulsed laser deposition at different substrate temperatures, ranging from 300 to 660 K. While the variation of the substrate temperature does not affect significantly the excellent Nb thin film adhesion to the Si(100) substrate surface, the increase of the substrate temperature up to 570 K promotes an improvement of the grown film in terms of morphology and roughness. Such improvement is achieved through the formation of wider columnar structures with a reduced superficial roughness, around 5 nm, as shown by scanning electron microscopy (SEM) and atomic force microscopy. The use of temperatures over 570 K increases the substrate roughness due to the formation of irregular structures inside the film, as observed by SEM cross section analysis, and does not produce a relevant improvement on the crystalline structure of the material.